Andreev reflection study of a new magnetic superconductor Mo3Sb7 in magnetic field - Dmitriev, V.M.; Rybaltchenko, L.F.; Ishchenko, L.A.; Khristenko, E.V.; Bukowski, Z.; Troć, R. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2007)
Andreev reflection in contacts based on a magnetic superconductorMo3Sb7in magnetic field has been investigated by the point-contact method. It is found that the behavior of the order parameter in the magnetic field Δ(H) is essentially dependent on the value of Δ, which varies widely (Δ(0,0) ≈ 0.01-0.31meV) for different contacts at practically invariant Tc. At high the dependence max(H)deviates slightly from the theoretical prediction applicable under the point-contact conditions. As the order parameter decreases, the deviation starts to increase and becomes very large when Δ approaches its minimum. Proceeding from the results obtained in this study and from the temperature measurements on Mo3Sb7performed formerly, we are inclined as before to assign the compound to the class of superconductors with anisotropic gap function. So, in no way can it be considered as conventional BCS-type superconductor. The upper critical field Hc2 ≈16.5 kOe found here is close to that obtained from magnetization measurements in another study. According to the estimation performed, the pair-breaking effect of the Pauli paramagnetism is rather weak in Mo3Sb7.